ANALISIS PENENTUAN HARGA POKOK PRODUKSI DENGAN METODE HARGA POKOK PESANAN PADA CV. CAHAYA BERKAH MADANI (UNIT NH COLLECTION) - Lia Sukma Dai Lukmana; Eko Triyanto (Jurnal Inovasi Penelitian, 2023)
This article has the title analysis of determining the cost of production using the cost of goods ordered method on CV. Madani Blessing Light. The purpose of this research is to analyze and find out the calculation of the cost of orders applied to CV. Madani Blessing Light. With reference to orders for batik suits by SMP Insan Mandiri. This research uses a qualitative descriptive method because this research uses facts or events and conditions that are currently happening at the company to obtain conclusions from research and suggestions that can be used for the company. In determining the cost of production, the company has not been able to classify exactly how many costs occur in the production process, especially direct labor costs and factory overhead costs, where these costs are actually very influential in determining the cost of production. In its application, the company imposes factory overhead costs that occur on ordered products based on predetermined rates. In this case, the determination of the factory overhead rate by the company is to charge it 15% of the cost of the raw materials used